Integration of organic electrochemical transistors and immuno-affinity membranes for label-free detection of interleukin-6 in the physiological concentration range through antibody–antigen recognition. Issue 33 (13th August 2018) - Gentili, Denis; D'Angelo, Pasquale; Militano, Francesca; Mazzei, Rosalinda; Poerio, Teresa; Brucale, Marco; Tarabella, Giuseppe; Bonetti, Simone; Marasso, Simone L.; Cocuzza, Matteo; Giorno, Lidietta; Iannotta, Salvatore; et al.
Abstract : A label-free immunosensor based on an organic electrochemical transistor integrated with an immuno-affinity membrane for cytokine detection at physiologically relevant concentrations is reported. Abstract : We demonstrate the label-free and selective detection of interleukin-6 (IL-6), a key cell-signaling molecule in biology and medicine, by integrating an OECT with an immuno-affinity regenerated cellulose membrane. The objective of the membrane is to increase the local concentration of IL-6 at the sensing electrode and, thereby, enhance the device response for concentrations falling within the physiological concentration range of cytokines. The OECT gate electrode is functionalized with an oligo(ethylene glycol)-terminated self-assembled alkanethiolate monolayer (SAM) for both the immobilization of anti IL-6 antibodies and the inhibition of non-specific biomolecule binding. The OECT gate/electrolyte interface is exploited for the selective detection of IL-6 through the monitoring of antigen–antibody binding events occurring at the gate electrode.